PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN DI KOPI SINGGAH BOGOR - Herawati, Dahlia (Sekolah Tinggi Ilmu Ekonomi GICI, 2024)
One industry that is still growing today is the food and beverage industry. This industry is a promising business because the market potential of the food and beverage business is very large because food and drink are basic human needs, so it will create extraordinary demand. Like the Bogor Singgah Coffee shop beverage business which until now has survived in the development of the business world with a level of intense competition, this business was founded because of people's passion and love for coffee, especially if you look at the way individuals allocate money and time which can describe lifestyle also occurs in the phenomenon of drinking coffee in a coffee shop which has recently been spreading. The purpose of this study was to determine and analyze the effect of the marketing mix on purchasing decisions at Kopi Singgah Bogor. The type of research used is survey research with a research method in the form of data collection using a questionnaire. The data analysis model used is simple linear regression analysis. The sample selection was carried out by purposive sampling. The sample amounted to 80 respondents. The regression test results show that 69.7% of purchasing decision factors can be explained by product, price, location, and promotion indicators while the remaining 30.3% is is explained by other factors not examined in this study. The t test results show that the marketing mix variable shows the results of the tcount analysis (13.520) where the ttable (1.665), so the marketing mix variable has a positive and significant effect on purchasing decisions at Kopi Singgah Bogor.